FULFILLMENT OF RESTITUTION RIGHTS TO TRAFFICKING VICTIMS CRIMINAL ACT (Study of Decision Number 322/Pid.Sus/2023/PN Jkt.Sel and Decision Number 667/Pid.Sus/2023/PN - Petricia Br Sembiring; Marlina; Yati Sharfina Desiandri (CV Rewang Rencang, 2024)
The crime of human trafficking has been regulated by Law Number 21 of 2007 concerning the eradication of the crime of trafficking. When the victims have experienced material and immaterial losses, restitution is one of the forms of assistance to victims of the crime of human trafficking. The research method used in this study is descriptive-analytical with a normative legal research type. Furthermore, the research data consists of primary and secondary data. Law Number 21 of 2007 regulates restitution for victims of human trafficking. Decision 322/Pid. Sus/2023/PN Jkt. Sel does not provide restitution, while Decision 667/Pid. Sus/2023/PN Kis does. Judges need to be consistent and objective in handling human trafficking cases so that justice is achieved. Decision 322/Pid. Sus/2023/PN Jkt. Sel is considered to have paid less attention to the facts of the trial, while Decision 667/Pid. Sus/2023/PN Kis is appropriate because the judge creates legal certainty. Legal certainty in a judge's decision must be based on relevant facts.